2021
DOI: 10.2147/ccide.s323428
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Correlates of Fissured Tongue Among Outpatients in Andkhoy City, Afghanistan: A Cross-Sectional Study

Abstract: Background: Fissured tongue is a common manifestation of the tongue, marked by the presence of multiple prominent grooves or fissures on the dorsal surface of the tongue. However, there is a lack of studies focusing on the prevalence and factors associated with fissured tongue among patients attending an outpatient clinic in Afghanistan. Aim: The purpose of the current study was to determine the prevalence and factors associated with fissured tongue and its effects on the general health of adult outpatients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…4 Contradicting with our result a study conducted in Afghanistan showed that fissured tongue coexistent with diabetes mellitus followed by hypertension. 17 In comparison, in the Dental Hospital Airlangga University, the prevalence of fissured tongue in healthy elderly (without degenerative diseases, including hypertension) also showed similar result with a percentage of 93.1%. 18 Based on the result of this study, elderly who take amlodipine were as many as 125 (8.57%) and in proportion with the numbers of participant who suffered fissured tongue.…”
Section: Discussionmentioning
confidence: 80%
“…4 Contradicting with our result a study conducted in Afghanistan showed that fissured tongue coexistent with diabetes mellitus followed by hypertension. 17 In comparison, in the Dental Hospital Airlangga University, the prevalence of fissured tongue in healthy elderly (without degenerative diseases, including hypertension) also showed similar result with a percentage of 93.1%. 18 Based on the result of this study, elderly who take amlodipine were as many as 125 (8.57%) and in proportion with the numbers of participant who suffered fissured tongue.…”
Section: Discussionmentioning
confidence: 80%
“…Fissures develop on the dorsal surface of the tongue due to inadequate glycemic control, immunological changes, alteration in microcirculation, and salivary flow. 34,37 Manifestations like fissure tongue were prevalent in patients with higher HbA1c levels, accounting to 91% of diabetic patients. The findings of our study are consistent with the results of the study done on the Japanese population by Hsu et al 20 Furthermore, in the current study, there was a greater prevalence of both yellow (57.6%) and pale yellow (29.4%) tongue coatings in patients having high levels of HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors are associated with these two patterns (Dafar et al, 2016 ). The geographic tongue is characterized by the loss of filiform papillae and by habitual factors, for example chewing tobacco (Assimakopoulos et al, 2002 ; Dafar et al, 2016 ); the genesis of fissures is unknown, discussing genetic factors and systemic diseases (Dawson, 1974 ; Eidelman et al, 1976 ; Guggenheimer et al, 2000 ; Hamrah et al, 2021 ; Marcoval et al, 2012 ; Monshi et al, 2021 ). The papillae in fissured tongues are preserved and the tongue shows a higher accumulation of inflammatory cells (Kullaa‐Mikkonen & Sorvari, 1986 ).…”
Section: Discussionmentioning
confidence: 99%